O projeto geoparque sertão monumental (Ceará, Brasil): relevância geomorfológica e cartografia de paisagens - Monteiro, Felipe Antônio Dantas (2024)
Embedded in the central backlands of the state of Ceará, Brazil, lies a monumental complex of semi-arid granitic landscapes. This territory, known as the Sertão Monumental Geopark Project (GSM), formed by the municipalities of Quixadá and Quixeramobim, stands out for its exceptional geodiversity. It features an extraordinary field of diversified and ornamented inselbergs (monoliths) adorned with tafoni, karren, flared slopes, gnammas, and other geomorphologies that tell the story of Earth’s evolution. As such, it deserves conservation for scientific studies, education, sustainable use, tourism, and other activities that promote territorial development. Pertinent to this context, we observe a new area of knowledge called Geoconservation emerged, which works interdisciplinary with relevant concepts such as Geodiversity, Geoheritage, Geotourism, Geoparks, among others. Currently, the GSM is distinguished as being a project for UNESCO Global Geoparks (UGGp). The UGGp are unique geographical areas, where their internationally significant geopatrimony is managed based on a holistic concept of protection, education, and sustainable development. This work aims to contribute to the Sertão Monumental Geopark Project, analyzing what is known about the Sertão Monumental and how its geomorphological relevance and landscape cartography can enhance the GSM. By doing so, it collaborates with this important project, seeking recognition of the territory’s significance and the coveted UNESCO Global Geopark seal.